Nutrition Counseling, Lipid Profile Improvement and Weight Loss in Obese Patients with Dyslipidemia - Salman, Salman; Hadi, Novian Swasono; Ntau, Liean A.; Olii, Nancy; Astuti, Siti Choirul Dwi (Research and Community Service Unit, Poltekkes Kemenkes Kupang, 2023)
Obesity with dyslipidemia is a serious problem because it risks various degenerative and metabolic diseases. The prevalence of obesity in Indonesia continues to increase every year, currently in the adult population reaching 21.8%. To prevent the onset of degenerative diseases and metabolic disorders, it is important to control obesity with dyslipidemia through weight loss and lipid profile improvement. This study aims to determine the effect of nutritional counseling in losing weight and improving lipid profiles in obese patients with dyslipidemia. This is a pseudo-experimental study with One group Pre and Post Test Design. The initial stage was the identification of obesity and lipid profile. In 100 respondents identified as obese, total cholesterol, LDL and triglycerides were examined. 40 obese respondents with dyslipidemia were determined as samples. The second stage was nutrition counseling intervention. The third stage of evaluation is the re-measurement of body weight and lipid profile. The research result is only 30 respondents participated in the evaluation. Average initial body weight was 75.11 kg and final body weight was 73.14 kg. Average weight loss was 1.97 kg. Average initial cholesterol 233.20 mg/dL and final cholesterol 224.70 mg/dL. Average cholesterol reduction of 8.5 mg/dL. Average initial LDL 152.37 mg/dL and final LDL 139.47 mg/dL. Average decrease in LDL 12.9 mg/dL Average initial triglycerides 161.23 mg/dL and final triglycerides 143.97 mg/dL. The average decrease in triglycerides is 17.26 mg/dL. The statistical test results showed a p-value = 0.000. There is an effect of nutritional counseling on weight loss and improvement of lipid profiles of obese patients with dyslipidemia.